2013
DOI: 10.4049/jimmunol.1201951
|View full text |Cite
|
Sign up to set email alerts
|

Class I Phosphoinositide-3-Kinases and Src Kinases Play a Nonredundant Role in Regulation of Adhesion-Independent and -Dependent Neutrophil Reactive Oxygen Species Generation

Abstract: Chemoattractant-induced reactive oxygen species (ROS) generation by adherent neutrophils occurs in two phases: the first is very rapid and transient, and the second one is delayed and lasts up to 30–40 min. We examined the role of phosphoinositide 3-kinases (PI3Ks) and Src-family kinases (SFKs) in these responses using human neutrophils treated with inhibitory compounds or murine neutrophils deficient of PI3Kγ or Hck, Fgr, and Lyn. Our studies show that PI3Kγ is indispensable for the early, fMLF-induced ROS ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 50 publications
(92 reference statements)
3
40
0
Order By: Relevance
“…Consistently with the evidence that Syk deficiency results in defective integrin-dependent ROS generation, but does not affect responses triggered by trimeric G protein-coupled receptor [38,39], we found that the early adhesion-independent fMLP-induced phase of ROS generation [see [26]] was equal in wild-type and Syk-deficient neutrophils (fig. 7g).…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Consistently with the evidence that Syk deficiency results in defective integrin-dependent ROS generation, but does not affect responses triggered by trimeric G protein-coupled receptor [38,39], we found that the early adhesion-independent fMLP-induced phase of ROS generation [see [26]] was equal in wild-type and Syk-deficient neutrophils (fig. 7g).…”
Section: Resultssupporting
confidence: 74%
“…The plates were read in a fluorescence microplate reader (Victor 3, PerkinElmer; Waltham, Mass., USA) with a filter setting of 485/535 nm (excitation/emission). Coating of the wells with fibrinogen was performed because we noticed that on plain plastic the SYTOX green signal detected in unstimulated cells displayed quite a high variability with different cell preparations probably due to neutrophil spreading on plastic [see [26]].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isoluminol-based chemiluminescence assays were prepared in Hank's balanced salt solution supplemented with 0.5 mM CaCl 2 and 5 mM d-glucose (HGCa) in the presence of horseradish peroxidase (HRP) and isoluminol in a temperature-controlled Multilabel Count Victor X5 (PerkinElmer). The assays were carried out in dark 96-well plates precoated with 250 µg/ml human fibrinogen in HGCa containing 100 µM isoluminol and 8 U/ml HRP 53,54 . Following the addition of 1 × 10 5 human neutrophils or 7.5 × 10 5 mouse neutrophils, the plates were left at 37 °C for 10 min and the reaction initiated by introducing the stimulus (see text for concentrations).…”
Section: Rapid Adhesion Assaysmentioning
confidence: 99%
“…Vav1 is a GEF that is primarily expressed in hematopoietic cells (Tong et al , 2013, Zenker et al , 2014. It has been reported that Vav1 can be phosphorylated in vivo by Src kinases (Fumagalli et al , 2013), suggesting that the guanine nucleotide-exchange activity of Vav1 can be modulated by tyrosine phosphorylation. Vav1 may also be regulated via the interaction of its PH domain with the lipid products of PI3K (Gambardella andVermeren, 2013, Navarro-Lerida et al , 2012).…”
Section: Introductionmentioning
confidence: 99%